Impact of previous disease-modifying treatment on safety and efficacy in patients with MS treated with AHSCT. Issue 8 (4th May 2022) - Kvistad, Silje Agnethe Stokke; Burman, Joachim; Lehmann, Anne Kristine; Tolf, Andreas; Zjukovskaja, Christina; Melve, Guro Kristin; Bø, Lars; Torkildsen, Øivind
Abstract : Background: Autologous haematopoietic stem cell transplantation (AHSCT) is a highly effective treatment for multiple sclerosis (MS). The impact of previous long-lasting disease-modifying treatments (DMT) for safety and efficacy of AHSCT is unknown. Objective: To explore whether previous DMTs with long-lasting effects on the immune system (anti-CD20 therapy, alemtuzumab and cladribine) affect treatment-related complications, long-term outcome and risk of new MS disease activity in patients treated with AHSCT. Methods: Retrospective observational study of 104 relapsing remitting patients with MS treated by AHSCT in Sweden and Norway from 2011 to 2021, grouped according to the last DMT used ≤6 months prior to AHSCT. The primary outcomes were early AHSCT-related complications (mortality, neutropenic fever and hospitalisation length), long-term complications (secondary autoimmunity) and proportion of patients with No Evidence of Disease Activity (NEDA-3 status): no new relapses, no MRI activity and no disease progression during the follow-up. Results: The mean follow-up time was 39.5 months (range 1–95). Neutropenic fever was a common AHSCT-related complication affecting 69 (66%) patients. There was no treatment-related mortality. During the follow-up period, 20 patients (19%) were diagnosed with autoimmunity. Occurrence of neutropenic fever, hospitalisation length or secondary autoimmunity did not vary dependent on the last DMT used prior to AHSCT. A total of 84 patients (81%) achieved NEDA-3 status, including all patients (100%) using rituximab, alemtuzumab or cladribine before AHSCT. Conclusion: This study provides level 4 evidence that AHSCT in patients previously treated with alemtuzumab, cladribine or rituximab is safe and efficacious.